Long-Term Stability and Safety of Transgenic Cultured Epidermal Stem Cells in Gene Therapy of Junctional Epidermolysis Bullosa - De Rosa, Laura; Carulli, Sonia; Cocchiarella, Fabienne; Quaglino, Daniela; Enzo, Elena; Franchini, Eleonora; Giannetti, Alberto; De Santis, Giorgio; Recchia, Alessandra; Pellegrini, Graziella; De Luca, Michele (Stem cell reports, 2014)
We report a long-term follow-up (6.5 years) of a phase I/II clinical trial envisaging the use of autologous genetically modified cultured epidermal stem cells for gene therapy of junctional epidermolysis bullosa, a devastating genetic skin disease. The critical goals of the trial were to evaluate the safety and long-term persistence of genetically modified epidermis. A normal epidermal-dermal junction was restored and the regenerated transgenic epidermis was found to be fully functional and virtually indistinguishable from a normal control. The epidermis was sustained by a discrete number of long-lasting, self-renewing transgenic epidermal stem cells that maintained the memory of the donor site, whereas the vast majority of transduced transit-amplifying progenitors were lost within the first few months after grafting. These data pave the way for the safe use of epidermal stem cells in combined cell and gene therapy for genetic skin diseases. •Long-term restoration of functional epidermis and epidermal-dermal junction•A defined number of transgenic stem cells sustain the regenerated epidermis•Human epidermal stem cells maintain the memory of the site of origin•No adverse events have been reported during a 6.5-year follow-up De Rosa et al. report a long-term follow up of ex vivo gene therapy of junctional epidermolysis bullosa by means of autologous genetically modified cultured epidermal stem cells. The epidermal-dermal junction and functional epidermis were restored. The transgenic epidermis was sustained by a discrete number of long-lasting, self-renewing epidermal stem cells that maintained the memory of the donor site.